Crime in tourism destinations: Research review - Lisowska, Agnieszka (Turyzm/Tourism, 2017)
Tourism has become a common phenomenon, very important for various reasons, especially for developing regions and countries, and which in consequence has been perceived as positive. However, increasingly commonly works have cast a slightly different look. Tourism leads to a temporarily increased number of people in a relatively small area, and contributes to the introduction of ‘strangers’ to local communities which can lead to problems such as crime. On the other hand, a higher risk of being a victim may lead to the reduced attractiveness of a given destination. A small number of studies in this field draw attention to this, concentrating on a general outline of their interdependence but specific urban tourist areas are rarely the subject of research. This review covers various works on the relationship between tourism and crime.